“You say you want to be transformed” : Jeanette Winterson and reader empowerment in The Powerbook and Art & Lies - Zhang, Youying (2013)
In her novels Art & Lies and The.Powerbook, Jeanette Winterson consistently fragments the narratives and foregrounds fictional contrivance to position readers as active participants in the generation of multivalent narratives about love and its meanings. Through her use of metafictional story-telling methods, overt fictional artifices and mise-en-abyme, Winterson disrupts numerous love narratives including her own in order to prompt her readers to question existing tropes and beliefs in love narratives. These techniques are explored through the Reader Response approach.